Vertical Stratification of fruit-feeding butterflies (lepidoptera : nymphalidae) in a secondary forest, Kota Samarahan, Sarawak - Asmaa, Bt Che Mohd Rosli. (Universiti Malaysia Sarawak (UNIMAS), 2013)
The diversity and vertical stratification (ground: l m above ground; canopy: 20-22m above ground) of the fruit-feeding butterflies were studied in a secondary forest located in the vicinity of UNIMAS East Campus, Kota Samarahan by using 10 baited traps. A single-rope technique was applied in 60 days sampling period. A total of 279 individuals f~om 33 species and four subfamilies were documented. Species diversity index was higher at canopy level with Shannon diversity index H'= 2.536. The overall total species richness and abundance reflected a declining pattern of Morphinae and Satyrinae which was observed as increasing heights and vice versa. The dominance was be represented by the Satyrine, Mycalesis anapita/ilcentia which is 21.5% (60 individuals) of the total number of individuals sampled. M. anapita was to be found at ground level. Nymphanlinae was the most specious subfamily at the canopy level representing 42.42% (15 specie ) of the total number of species, while Satyrinae was the most abundant subfamily, representing 41.58%. Charaxinae was found to be the lowest in both abundance and species richness. The secondary forest resulted a high proportion of Nymphalinae to canopy level and various pattern distribution of butterflies also were be observed.